2018
DOI: 10.1590/0034-7167-2017-0314
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety and infection control: bases for curricular integration

Abstract: Patient safety related to infection prevention and control practices is present in the curriculum of health undergraduate courses, but is not coordinated with other themes, is taught sporadically, and focuses mainly on hand hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
(48 reference statements)
0
14
0
1
Order By: Relevance
“…[8,9] Accordingly, the undergraduate nursing program should prepare those intern nurses with the necessary knowledge, skills and attitudes related to safe nursing practice. [10] Therefore, it has been reported that IPC education needs to be included in the orientation program of all healthcare staff with a special focus on novice nurses, doctors and the internship students [11] and it has to be considered as a part of their personal development plans. However, various studies have been reported that; nursing students have a low level of knowledge regarding IPC and poor transfer of that knowledge to their clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Accordingly, the undergraduate nursing program should prepare those intern nurses with the necessary knowledge, skills and attitudes related to safe nursing practice. [10] Therefore, it has been reported that IPC education needs to be included in the orientation program of all healthcare staff with a special focus on novice nurses, doctors and the internship students [11] and it has to be considered as a part of their personal development plans. However, various studies have been reported that; nursing students have a low level of knowledge regarding IPC and poor transfer of that knowledge to their clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the elements which characterize the patient's identification, the percentage of prescription receipts which presented the full name (74.7%) and age (0.2%) were much less than ideal (100%). In the context of patient safety, correct identification is essential in handling medication, since the chances of other errors occurring (e.g., dose, administration route, medication and wrong patient) are maximized in the absence of the patient's name in a legible manner (10)(11) . The percentage (98.3%) with regard to the issue date of the prescription receipt was close to the ideal (100%), although still lower than that recorded (99.3%) in a study conducted in Minas Gerais state, Brazil (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Similar deficiencies in medical curricula regarding safety as it pertains to IPC practices have recently been highlighted in a systematic review involving higher education institutions. 20 Junior nurses by contrast received rigorous practical training involving AT, PI and in particular, HH, and were accordingly well assessed in these areas. Although barriers existed to the comprehensive tracking of IPCrelated teaching in the later years of both medicine and nursing training, it was clear there was a need for more formal scheduled IPC instruction in the clinical setting where students complete their undergraduate education.…”
Section: Discussionmentioning
confidence: 99%